2020
DOI: 10.22159/ijap.2020v12i6.38927
|View full text |Cite
|
Sign up to set email alerts
|

Development of Binary and Ternary Complex of Cefuroxime Axetil With Cyclodextrin for Improving Pharmaceutical Characteristics

Abstract: Objective: The current research objective is systematic development and characterization of binary and ternary inclusion complexes of cefuroxime axetil with β-cyclodextrin to improve its pharmaceutical characteristics by using the kneading method. Methods: Phase solubility study was carried out using Higuchi and Connors method. Based on its result, binary complexes of cefuroxime axetil with different ratio of β-cyclodextrin were developed and characterized using differential scanning calorimeter (DSC), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…PS, FTIR, DSC, PXRD, UV-VIS [50] Cefuroxime axetil HP-β-CD Ten human volunteers were used to assess the oral suspensions' flavors. The study employed the pure medicine cefuroxime axetil as the benchmark, and it also compared the formulations using a market sample.…”
Section: Lomefloxacin Hydrochloride Hp-β-cdmentioning
confidence: 99%
“…PS, FTIR, DSC, PXRD, UV-VIS [50] Cefuroxime axetil HP-β-CD Ten human volunteers were used to assess the oral suspensions' flavors. The study employed the pure medicine cefuroxime axetil as the benchmark, and it also compared the formulations using a market sample.…”
Section: Lomefloxacin Hydrochloride Hp-β-cdmentioning
confidence: 99%
“…A similar attempt to include cefuroxime axetil in β-CD with and without L-arginine showed that the ternary system performed better than the binary system, offering much better solubility and dissolution rate than cefuroxime axetil alone [ 71 ]. The ternary system was also investigated as a combination of cefuroxime axetil, β-CD, and PVP K-30, and showed the best properties compared to the binary complex and the pure drug substance, with in vitro release tests >85% dissolution within 30 min [ 72 ].…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…Moreover, TA showed that the kneaded product loses less mass, demonstrating that the product obtained by kneading is more stable [75] due to strong electrostatic interactions between PVP-K30 and MβCD, as shown in the IR spectrum. PVP-K30 was also used in a multicomponent complex with βCD and cefuroxime axetil, to improve the latter's pharmaceutical characteristics, via the kneading method [77]. Cefuroxime axetil is a prodrug of cefuroxime cephalosporin, which is used for pharyngitis, respiratory tract infections, acute bacterial otitis, simple skin infections and urinary tract infections.…”
Section: Polyvinylpyrrolidonementioning
confidence: 99%
“…It is a BCS class II drug, so it has less aqueous solubility with an oral bioavailability of 37% on an empty stomach, which increases to 52% if taken after meals. In this multicomponent complex of cefuroxime axetil with βCD, PVP-K30 can act as a ternary PVP-K30 was also used in a multicomponent complex with βCD and cefuroxime axetil, to improve the latter's pharmaceutical characteristics, via the kneading method [77]. Cefuroxime axetil is a prodrug of cefuroxime cephalosporin, which is used for pharyngitis, respiratory tract infections, acute bacterial otitis, simple skin infections and urinary tract infections.…”
Section: Polyvinylpyrrolidonementioning
confidence: 99%
See 1 more Smart Citation